Lipoprotein(a) and other risk factors in dyslipidemic patients with and without heart failure - Joanna Lewek; Bozena Sosnowska; Agata Bielecka-Dabrowa; Karina Mierczak; Weronika Adach; Maciej Banach (Archives of Medical Science)
Introduction Material and methods Results Conclusions